Die invloed van 'n metode van geleide ontdekking, waarby die geskiedenis van wiskunde integreer word, op die houding van St. 9-leerlinge teenoor meetkunde. - Cronje, Lefina Susanna (My University, 1991)
There is widespread concern over some of the problems encountered in the teaching of Euclidean Geometry in secondary schools and also over the fairly negative attitudes experienced by pupils towards Geometry. This piece of research was designed to improve attitudes of Std.9 pupils towards Euclidean Geometry by making use of guided discovery and the integration of the history of Mathematics into the teaching method used. The latter was done in order to humanise the subject and to make it more interesting to pupils who otherwise experience it as very rigid and abstract. Active participation of pupils in developing the Geometry was central to the method employed. The outcome of the research was positive. It showed that attitudes towards Geometry can be improved if a deliberate attempt to do so is made. The results of this research suggest guidelines by which the teaching of Euclidean Geometry in secondary schools could be improved.
NAVORSINGSVERSLAG voorgele ter gedeeltelike vervuiling van die vereiste vir die graad MAGISTER IN NATUURWETENSKAPPE in die FAKULTEIT NATUURWETENSKAPPE aan die UNIVERSITEIT VAN DIE WITWATERSRAND.
Keywords: Geometry -- Study and teaching.; Mathematics -- study and teaching